STRESS FACTORS IN IN-SERVICE TEACHER TRAINING PROGRAMS - Yeni Afrida; Iswantir; Fadhilla Yusri; Sabarrudin (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2024)
In-service teacher education has an important role in facing the challenges posed by the COVID-19 pandemic, including helping teachers prepare to face new challenges arising from the pandemic, improving the quality of learning, building online teaching skills, supporting students with ideals and hopes and building communities Study. This allows students to get access to quality education even though they are at home. Understanding the impact of the transition from blended learning to online learning is critical to seeing how this change affects in-service teacher training program students, particularly in terms of their stress levels. This research aims to reveal the phenomenon of stress experienced by students while undergoing a professional teacher training program as well as the indications and causes in terms of class, age, gender and place of origin. The type of research is quantitative comparative, the population consists of 418 people and 180 people as research samples were taken using purposive sampling. The results of the research show that Madrasah and PPG PAI, there is no significant difference in stress, nor in terms of age, no significant difference, the 43–49-year age group has a higher average stress score compared to others, with the average stress score was 71.10. Judging from the place of origin, there are differences in the stress felt by students. The average stress score for students in West Sumatra is higher than in the provinces of North Sumatra, Riau, Jambi, Aceh, Central Java and South Sulawesi, as well as in terms of gender.